Hasil Belajar Siswa Ditinjau Dari Keaktifan Bertanya Dan Kemampuan Berkomunikasi Dalam Mata Pelajaran Ipa Pada Kelas Viii Di Smpn 1 Ngemplak BoyolaliSemester Ii Tahun Ajaran 2014/2015 - DERMAWAN, ZENDI; , Dra. Hariyatmi, M.Si (2015)
Learning outcomes is something that is achieved or obtained by students thanks to the effort or mind which it is expressed in the form of mastery, basic knowledge and skills contained in the various aspects of kehidupa so apparent on the individual usage behavior changes quantitatively. This study aims to determine: Effect of liveliness ask and communication skills of students towards science learning outcomes in SMPN 1 Ngemplak Boyolali academic year 2014/2015. This research is a quantitative study with explanatory research type uses one path analysis test (One Way Annova). This study population is class VIII student at SMPN 1 Ngemplak Boyolali academic year 2014/2015. Samples of this research is class VIII A, VIII C and VIII E at SMPN 1 Ngemplak Boyolali. Data collection techniques were used that through observation and documentation. The result showed that: Value Sig. 0.014 <0.05 then the IPA learning results are influenced by the activity of asking and communication skills of students in SMPN 1 Ngemplak Boyolali academic year 2014/2015. Thus it was concluded that: IPA learning outcomes are influenced by the activity of asking and communication skills of students in SMPN 1 Ngemplak Boyolali academic year 2014/2015.